Analysis of Clinical Course and Vaccination Influence on Serological Response in COVID-19 Convalescents - Justyna Adamczuk; Piotr Czupryna; Justyna Dunaj-Małyszko; Ewelina Kruszewska; Sławomir Pancewicz; Karol Kamiński; Karol Borawski; Sambor Grygorczuk; Anna Moniuszko-Malinowska (Microbiology Spectrum, 2022)
ABSTRACT Our goal was to assess the anti-SARS-CoV-2 antibodies presence in COVID-19 convalescents and assess the differences in anti-SARS-CoV-2 antibodies production regarding the disease severity, sex, vaccination, and assess the correlation between anti-SARS-CoV-2 antibodies production and inflammatory parameters. Three hundred twenty-two COVID-19 patients (282 hospitalized and 40 patients with oligosymptomatic COVID-19 isolated at homes) were included in the study. Blood was taken at 4 time points: during hospitalization, 1 month, 3 months, and 6 months. Detection of SARS-CoV-2 antibodies was performed with LIAISON SARS-CoV-2 S1/S2 IgG tests (DiaSorin, Italy). Clinical and laboratory parameters were compared. Significant differences between higher anti-SARS-CoV-2 antibodies titer in symptomatic patients 3 months after infection (III sample) and significantly higher ratio II/I in symptomatic patients were observed. Subgroup analysis based on sex showed differences only in laboratory tests, not in serological. Analysis of the results of serological tests showed significant differences in ratio IV/I and a significant increase in antibodies level after vaccination. The most significant rise was observed between the 3rd and 6th month when the patients received a vaccination. Immunological response after COVID-19 infection lasted over 6 months in all patients, although antibodies titers were significantly higher in patients with a history of severe COVID-19 and vaccinated patients. Immunological response after COVID-19 infection did not depend on sex. There was a significant correlation between anti-SARS-CoV-2 antibodies production and the degree of inflammation in the acute phase of the disease (inflammatory parameters in blood and severity of lung affection in CT). IMPORTANCE The results of our study confirm the knowledge on immune response in the Polish population and add new information regarding correlations with the severity of the disease. The data in the literature concerning the correlation between antibodies response and sex are ambiguous, and we did not observe differences between antibodies production and gender, which also adds new information.